Pandangan M. Natsir Tentang Demokrasi: Kajian Pemikiran Politik Islam - Muliati, Indah (TINGKAP, 2015)
This article discusses M. Natsir view on the concept of democracy in Islam. In the map of Islamic political thought, there are differing views on the concept of democracy from the West. No group has refused flatly to the correlation of Islam with the democracy, but there are also groups that accept the correlation of Islam with the concept of Western democracy. As one of the leaders of political Islam in Indonesia M. Natsir did not totally reject Western democracy. M. Natsir offers a slightly different concept of democracy known as Theistic Democracy. M. Natsir view of theistic democracy try to reconcile the theory of popular sovereignty with the sovereignty of God. M. Natsir rejected the system of theocracy and the secularization, but accepted the idea of nationalism. Additionally democracy in view M. Natsir have to walk on the following principles: monotheism, fraternity, equality, and ijtihad.Kata Kunci: Democracy, Islamic Democracy, Western Democracy